Anatomical variations in Eurasian wolf (Canis lupus lupus) (Carnivora: Canidae) of the salivary glands: A histological and histochemical investigation - Joanna Klećkowska-Nawrot; Karolina Goździewska-Harłajczuk; Krzysztof Stegmann; Arkadiusz Dziech; Dariusz Łupicki; Gabriela Jędrszczyk; Igor Jucenco; Karolina Barszcz (PLoS ONE, 2025)
The study involved a gross anatomical description of the parotid gland, mandibular gland, monostomatic sublingual gland, polystomatic sublingual gland, and zygomatic gland in 12 adult Eurasian wolves (Canis lupus lupus) (wild free-ranging individuals and their zoo counterparts), including their morphometry and microscopic evaluation using hematoxylin & eosin, mucicarmine, azan trichrome, PAS, AB pH 1.0, AB pH 2.5; AB pH 2.5/PAS, and HDI stainings. Topographically, the salivary glands were located similarly to those of other terrestrial Carnivora. The parotid gland in all wolves had a shape similar to a trapezoid (four angles). The parotid duct opened onto the fourth upper premolar (P4). The parotid gland was a branched alveolar complex that produced serous secretion. In captive specimens, the mandibular gland was a complex branched tubular gland producing mucous secretion, while in free-ranging wolves it was a branched tubuloalveolar gland producing mucoserous secretion. The monostomatic sublingual gland in free-ranging wolves was a complex branched tubuloalveolar gland that produced seromucous secretion, while in captive wolves, it revealed a mucoserous secretion character. The polystomatic sublingual gland consisted of several independent packets (from 6–7 to 7–8) and was a complex branched tubuloalveolar gland with seromucous secretion. The zygomatic duct opened onto the last upper molar tooth (M3), and this gland was a complex branched tubular gland producing mucous secretion. The anatomical and histological similarities between the salivary glands of the oral cavity in captive and free-ranging wolves, compared to other terrestrial carnivores, provide valuable insights for veterinary treatments and understanding pathological conditions. These findings emphasize the need for further research on diverse populations of wolves and related species within the Canidae family to better understand the influence of diet on salivary gland morphology.